PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG (Studi Kasus pada Pengguna Jasa Taksi Kosti Semarang) - Mutami M; Agus Hermani DS (Universitas Diponegoro, 2019)
Kosti Taxis as one of the transportation companies still have consumers who have a low repurchase interest. This is due to the increasing number of online taxis that have sprung up at lower prices and the quality of services is not much different This study aims to find out how the influence provided by price and quality of service on the repurchase interest of Kosti Taxis. The type of sampling uses purposive sampling. The type of research used is the type of explanation (explanatory research) while the data collection technique uses a questionnaire with the Likert measurement scale. The number of samples used in this study were 100 respondents. The results of this study indicate that the variable price and service quality each have a significant, strong and positive influence on repurchasing interest. Two variables have been tested in stages or together show the results that the price variable (0.508) and service quality (0.102) simultaneously have a positive influence on the repurchase intention variable. The amount of contribution owned by the price variable is greater than the amount of contribution owned by the quality of service, the coefficient of determination (R²) for the price variable of 45.4% and service quality of 16%.